ONLINE LEARNING AMONGST UNIVERSITY OF NAIROBI UNDERGRADUATE STUDENTS AMID COVID-19 PANDEMIC, KENYA: Received: 05th July 2021; Revised: 20th August 2021, 20th February 2022, 5th March 2022; Accepted: 9th March 2022 - Nyaegah, Ouru John (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Acquisition of Education is crucial in an individual and society’s development which cuts across different stages of human growth with specific and achievable goals. The survey sought to establish the extent to which the Corona Virus Pandemic influenced the adoption of Online learning among undergraduate students of the University of Nairobi. The study had five objectives which focused on learners’ attitudes towards the adoption of virtual learning, how they learned online while coping with online challenges. A total of 232 students were used while the Spear-man Coefficient of Correlation Formula was applied to test research instruments’ reliability. Data was analyzed and presented in tabular, graphic, and percentages forms. The study established that 109 respondents forming 46.98% didn’t know online learning existed, while 34 forming 14.66% felt it was impossible to learn online. Further, 45 respondents forming 19.40% felt the method was not suitable for examinations while 44 (18.96%) preferred face-to-face teaching. Respondents used Google Meets and Google Classroom to learn. Despite the university ensuring learning continued online, 151 students forming 65.09% faced unreliable electricity, internet unreliability, and unfavorable study environments. The survey recommended that strategies were urgently needed for building a Resilient Education System to enhance learning in the university